Abolition and Empire in Sierra Leone and Liberia - Everill, B. (Cambridge Imperial and Post-Colonial Studies Series, 2013)
Bronwen Everill offers a new perspective on African global history, applying a comparative approach to freed slave settlers in Sierra Leone and Liberia to understand their role in the anti-slavery colonization movements of Britain and America.